Estudo da viabilidade de emulsões a base de óleos vegetais para uso em processos de usinagem de liga de alumínio 6061 - Ferreira, Caroline Carvalho (2023)
Excessive wear caused to mechanical components has been a worrying factor in the industrial environment. In the scope of industrial machining, cutting fluids are used, compounds that, among other purposes, serve to reduce the wear of cutting tools, through lubrication, prolonging their useful life. Traditionally, these inputs use mineral oils, mainly petroleum derivatives, as a lubricant, being non-renewable and with the potential to pollute the environment and cause harm to workers. Thus, as an alternative, there are vegetable oils, which are more sustainable, renewable and biodegradable. In this context, the present study aims to analyze the tribological behavior of wear in a pin-disc test of aluminum alloy 6061 parts, using different emulsions based on castor oil, cotton and tea tree essential oil. For that, tests were carried out in a pin-disc type tribometer, from the State University of Ponta Grossa (UEPG), with eight samples, six with fluids based on castor oil, cotton and tea tree essential oil, one with fluid commercial and one dry. The mass of the specimens (discs) of each sample was measured before and after the tests to perform volume loss and wear coefficient calculations. The surfaces of the specimens of each of the samples were also evaluated by means of Scanning Electron Microscopy (SEM). The results of the loss of volume and the coefficient of wear showed that the tests carried out with fluid produced less wear compared to the one carried out dry, while all fluids based on tested vegetable oils obtained a coefficient of wear lower than the commercial fluid, with the exception of sample 3. The best result obtained was with sample 2 (k = 0.0421 mm³/N.). The images generated via SEM corroborated the results found through the wear coefficient, demonstrating that the main wear mechanism in the tests was abrasion. All samples that used fluid showed a uniform wear track, in depth and width, unlike the sample with dry test, in which the wear occurred irregularly, confirming the lubricity of the fluids used. In this way, it was concluded that castor and cottonseed vegetable oils, in addition to tea tree essential oil, can be used in the composition of cutting fluids, replacing mineral oils from fossil sources, being a more sustainable alternative.